2002
DOI: 10.1258/135763302320118861
|View full text |Cite
|
Sign up to set email alerts
|

Videoconferencing for continuing medical education: from pilot project to sustained programme

Abstract: Videoconferencing has been used to provide distance education for medical students, physicians and other health-care professionals, such as nurses, physiotherapists and pharmacists. The Dalhousie University Office of Continuing Medical Education (CME) has used videoconferencing for CME since a pilot project with four sites in 1995-6. Since that pilot project, videoconferencing activity has steadily increased; in the year 1999-2000, a total of 64 videoconferences were provided for 1059 learners in 37 sites. Vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Videoconferencing is widely used in continuing medical education, and studies have demonstrated it is an effective and efficient method to deliver teaching in rural settings [1][2][3][4][5][6][7][8]. With our ever-expanding technology driven society, videoconferencing seems an appealing option to deliver teaching [2].…”
Section: Introduction mentioning
confidence: 99%
“…Videoconferencing is widely used in continuing medical education, and studies have demonstrated it is an effective and efficient method to deliver teaching in rural settings [1][2][3][4][5][6][7][8]. With our ever-expanding technology driven society, videoconferencing seems an appealing option to deliver teaching [2].…”
Section: Introduction mentioning
confidence: 99%
“…23 Technical quality is important, 24,25 but other components such as planning, faculty development, technical support and evaluation need to be considered as well. 26 There has been systematic development of quality standards for distance education in other fields which use technology to educate learners at a distance. However, the diffusion of this work into the medical field has been slow, 27 which is regrettable because fields like telemedicine can greatly benefit from these standards.…”
Section: Introductionmentioning
confidence: 99%
“… and general(25) 2,4,5,7,8,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] evaluation methods. The papers in the technical group were further subdivided into groups according to the environment, laboratory(11), and clinical(8), where the experiments had been conducted.…”
mentioning
confidence: 99%